Gender Differences in Psychological and Behavioral Responses of Infected and Uninfected Health-Care Workers During the Early COVID-19 Outbreak - Huang, Qiao; Luo, Li-Sha; Wang, Yun-Yun; Jin, Ying-Hui; Zeng, Xian-Tao (Frontiers in Public Health, 2021)
Objective: Understanding gender differences in responses of healthcare workers (HCWs) to COVID-19 outbreak is an effective way to promote customized supports. Methods: During February 2020, 103 HCWs infected with COVID-19 (64 females and 39 males) and 535 uninfected HCWs (383 females and 152 males) were recruited in a cross-sectional study. Level of attention, 6 emotional status and self-evaluation of 8 protective measures were recorded. Multivariable Firth’s logistic regressions were applied to explored independent effect of gender. Results: During early outbreak, female HCWs were more likely to give greater attention, adjusted OR:1.92 (95%CI 1.14 to 3.23) in total HCWs. Higher proportion of anxiety was observed in female HCWs, adjusted OR:3.14 (95%CI 1.98 to 4.99) for total HCWs, 4.32(95%CI 1.32 to 14.15) for infected HCWs and 2.97(1.78, 4.95) for uninfected HCWs. Proportion of pessimism, fear, full of fighting spirit and optimism were low and no gender differences were observed. During later outbreak, majority of HCWs reported being very familiar with 8 protective measures after training, proportion of high self-evaluation in hand hygiene, wearing gloves and surgical mask increased independently in female HCWs, adjusted ORs were 3.07 (95% CI 1.57 to 5.99), 2.37 (95% CI 1.26 to 4.49), and 1.92 (95% CI 1.02 to 3.62), respectively. Infection status amplified gender difference in anxiety, hand hygiene and gloves wearing. Conclusion: Female HCWs perceived the outbreak seriously, effective emotional and psychological wellness should be targeted at female HCWs preferentially, male HCWs should be encouraged to express their feelings and be further trained.